Assessing adherence to treatment guidelines and complications among atrial fibrillation patients in the United Arab Emirates - Ayash, Bayan; Malaeb, Diana; Hallit, Souheil; Hosseini, Hassan (Frontiers in Cardiovascular Medicine, 2024)
Background: Atrial fibrillation (AF), a potential trigger for stroke development, is considered a modifiable condition to halt complications, decrease mortality, and prevent morbidity. CHA₂DS₂-VASc and HAS-BLED scores are categorized as risk assessment tools which estimate the risk of thrombosis development and assess major bleeding among atrial fibrillation patients. Objectives: Our study aims to assess the adherence to post-discharge treatment recommendations according to CHA₂DS₂-VASc score risk group and evaluate the impact of CHA₂DS₂-VASc score and HAS-BLED score risk categories on death, length of hospital stay, complications, and hospital readmission among United Arab Emirates patients. Methods: It was a multi-centre retrospective study conducted from November 2022 till April 2023 in United Arab Emirates. Medical charts for AF patients were assessed for possible enrolment in the study.Results: A total number of 400 patients were included with a mean age of 55 (±14.5) years, majority being females (67.8%), and most had CHA₂DS₂-VASc and HAS-BLED scores in the high category (60% and 57.3% respectively). Our study showed that adherence to treatment recommendation upon discharge was 71.8%. The bivariate analysis showed that patients with a high CHA₂DS₂-VASc score had a significantly higher risk of death (p-value of 0.001), hospital readmission (p-value of 0.007), and complications (p-value of 0.044) versus the low and moderate risk group pat with a p-value <0.05. Furthermore, our findings showed that the risk of death (0.001), complications (0.057), and mean hospital stay (0.003) were significantly higher in the high HAS-BLED risk score compared to both low and moderate categories. Hospital stay was significantly higher in CHA₂DS₂-VASc and HAS-BLED high risk score categories compared to low-risk category with a p-value <0.001.Our study concluded that the adherence to treatment guidelines in atrial fibrillation patients was high and showed that patients received the most effective and patient-centred treatment. In addition, our study concluded that the risk of complications and mortality was higher in high-risk category patients.